LOCALLY CARRAGEENAN TESTED FOR ITS FOOD GRADE BY FOOD AND AGRICULTURE ORGANIZATION METHOD - Indriyati, Wiwiek; Iskandar, Yoppi; Burhanuddin, Wildan Fawzi; Mustarcihie, Resmi (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: This study aims to determine whether seagrass lalamakan (Dictyota dichotoma), ades (Gelidium sp.), agar (Gracilaria sp.), and saribuhu (Sargassum sp.) obtained from the Sindangkerta beach, Tasikmalaya, can produce carrageenan food grade according to the Food and Agriculture Organization (FAO), Food Chemical Codex (FCC), and European Economic Community (EEC). Methods: Seaweed was extracted with distilled water and 0.1N KOH at high temperature (90Â°C). The extract was tested for its characteristics such as solubility test, test sulfate, gel formation, and its infrared (IR) spectrum. Results: The yield obtained from solvent extraction with distilled water ranged from 21% to 27%, whereas for 0.1N KOH solvent between 10% and 11% by weight. The results of the study indicated that the fiber obtained from both extractions was carrageenan, as shown by the results of the solubility test, the formation of gel and the infrared spectrum showed a sulfate ester, 3,6-anhydrogalactose, galactose-4-sulfate, and 3,6-anhydrogalactose-2- sulfate which was characteristic of carrageenan. IR spectrum confirmed the availability of carrageenan. Results of the sulfate test content in all sample fibers using either distilled water or 0.1N KOH were below 15.0%. Conclusion: These results indicated that the generated carrageenan did not meet food grade standards set by the FAO, FCC, and EEC which was 15- 40%. However, in fact, the carrageenan from the Sindangkerta beach has been produced and marketed in the local market.